Antioxidant activity of fresh and dried extracted herbs mixture of Psidium guajava, Pteridophytes, Cymbopogon, and Pandanus amaryllifolius / Ummi Kalthum Ibrahim and Amirah Adniruddin - Ibrahim, Ummi Kalthum; Adniruddin, Amirah (Universiti Teknologi MARA Shah Alam, 2018)
This study aims to investigate the effect of solvent concentration and extraction temperature on antioxidant activity of fresh and dried mixture of Psidium guajava, Pteridophytes, Cymbopogon, and Pandanus amaryllifolius. The samples were extracted using different concentration of methanol (0, 30, 50,and 70% (v/v)) in a shaking water bath at temperature of 60 °C and 90 °C for 30 minutes. From the results, the antioxidant activities were dependent on the solvent concentration and the temperature during extraction. The condition of both samples demonstrated different antioxidant activities. The highest antioxidant activities were found at 30% (v/v) methanol concentration and 60 °C indicating by the scavenging percentage of 53.85% and 65.93% for fresh and dried mixture, respectively. However, 70% (v/v) of methanol concentration exhibited the lowest antioxidant activities of fresh and dried mixture, showing 29.67% and 42.86%, respectively. Overall, the antioxidant activity in oven dried samples is higher than in the fresh samples. Other than that, GC-MS analysis presented the octen-1-ol,3,7-dimethyl (0.240%), cis-á terpineol (0.334%) and 6-octenal, 3,7-dimethyl (0.205%) as a major component in the extracts.